Socio-cultural Study of Written Invitation Cards in Iraqi Society - Mohammed Ahmed, Samara (Opción, 2019)
The present study explores the nature of analyzing invitation cards in Iraqi society from a sociocultural point of view . It attempts to systemize the various generic written invitation cards which are used for the purpose of inviting in Iraqi society and to highlight the socio – pragmatic constraints governing their use . The major aspects of inviting were examined :- inviting , style of writing and the types of the cards . The problem of this study is the difference between written and spoken wedding invitation . Invitation is the most important part in in Iraqi society because it clarifies or reflects the civility and the politeness of the inviter to the invitees . There is a big differences between spoken and written invitation . Most people in some societies tend to use spoken invitation which is the opposite of written invitation card. Written invitation is more respectable and more acceptable way for invitation . Written invitation make the invitees feel happy , feel with respectability and also this form of invitation stimulate them to open the invitation and read it although they know what will be written inside it and this form of invitation pay most of the invitees to retained the written cards special feelings when they read a wonderful phrases inside . This study is intended to quantitatively and qualitatively conduct a type of analysis for the purpose of determining discourse structures and key linguistic patterns which characterize the moves of the type of Arabic invita- tion cards produced in Iraqi society. This study aims at differentiating between different types of written invitation cards in order to determine what the generic components that have in comm.Particularly, it aims at showing the effects of some socio-cultural and pragmatic factors that may determine the content and structure of such written forms of invitations. This study show different written invitation types in Iraq through identify- ing various generic and schematic structures , linguistic features and also communicative functions .This study concludes that the use genre move analysis illustrate how the logical sequence of ideas is bound up by a set of writing conventions and social norms and by the use of these generic moves different types of cards can be identified here.